2014
DOI: 10.1186/1471-2377-14-121
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of injury of the corticospinal tract and corticoreticular pathway in hemiparetic patients with putaminal hemorrhage

Abstract: BackgroundNo study on the characteristics of injury of the corticospinal tract (CST) or corticoreticular pathway (CRP) in patients with putaminal hemorrhage has been reported. In this study, using diffusion tensor tractography, we attempted to investigate the characteristics of injury of the CST and CRP in hemiparetic patients with putaminal hemorrhage.MethodFifty seven consecutive patients with putaminal hemorrhage and 57 healthy control subjects were recruited for this study. Diffusion tensor imaging was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
1
29
1
Order By: Relevance
“…In addition, the intact PMC showed better recovery in terms of mobility and motor function of the hip [50]. Motor functions of patients with injury to both the CST and CRP were significantly poorer than those in patients with injury to either the CST or CRP [44]. Putaminal hemorrhage frequently accompanies injuries to both the CST and CRP, and the CRP appears to be more vulnerable than the CST.…”
Section: Motor Recovery With Lsm In Stroke Patientsmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, the intact PMC showed better recovery in terms of mobility and motor function of the hip [50]. Motor functions of patients with injury to both the CST and CRP were significantly poorer than those in patients with injury to either the CST or CRP [44]. Putaminal hemorrhage frequently accompanies injuries to both the CST and CRP, and the CRP appears to be more vulnerable than the CST.…”
Section: Motor Recovery With Lsm In Stroke Patientsmentioning
confidence: 90%
“…Putaminal hemorrhage frequently accompanies injuries to both the CST and CRP, and the CRP appears to be more vulnerable than the CST. These findings suggest the need for evaluating both the CRP and the CST in patients with putaminal hemorrhage [44].…”
Section: Motor Recovery With Lsm In Stroke Patientsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, other studies could not describe the status of the CST clearly (8, 40, 41). In 2013, Yeo et al reported on a patient who showed proximal weakness (MRC scores: shoulder abductor, 3 + ; hip flexor, 3 + ) following traumatic contusional hemorrhage (41, 43).…”
Section: Functions Of the Crtmentioning
confidence: 98%
“…Several studies have reported on the characteristics of motor weakness due to CRT injury in patients with brain injury (7, 8, 40, 41). However, precise estimation of the portion of the affected motor function for which the CRT is responsible is difficult because patients with brain injury usually have concomitant simultaneous injuries of other neural tracts associated with motor function such as the CST or the corticofugal tracts from the secondary motor area (6, 42).…”
Section: Functions Of the Crtmentioning
confidence: 99%